Pengembangan Media Pembelajaran Video Animasi Berbasis Aplikasi Canva Pada Kelas V - Nabila Aprilia; Iyan Irdiyansyah; Santa Santa (STKIP Andi Matappa Pangkep, 2023)
This research is a Research and Development (RnD) research. This research aims to find out the development of learning media based on the Canva application. This research was conducted at SDN Layungsari 1 Kota Bogor Class V C in July odd semester. The feasibility of this learning media is proven through the results of expert validation and student responses. The validation results of this learning media expert were declared feasible for use with the results of data analysis from the material expert questionnaire obtaining a percentage result of 98%, which means it is very feasible to use. Media experts earned a percentage of 92.8%, which means that the product developed is very feasible to use. Linguists obtained a percentage result of 80%, which means that the prosuk is very feasible to use. And based on a limited trial conducted on class V students as many as 32 students received a good response with a percentage of 85.62% meaning that this product is very suitable for use. Based on the results of the research above, it can be stated that canva application-based learning media is declared suitable for use in SDN Layungsari 1 Kota Bogor.